Domains of attraction of walking and running attractors are context dependent: illustration for locomotion on tilted floors - Frank, Till (International Journal of Scientific World, 2015)
There is a general consensus that gaits of humans and animals can be considered as spatio-temporal patterns emerging via self-organization. In line with synergetics, a theory of pattern formation and self-organization founded by Haken, an amplitude equation model for human run-walk gait transitions is presented. The model allows for a definition of two distinct attractors representing walking and running. In particular, the size of the two attractors in the space of locomotion speed can be determined as a function of the model parameters. Furthermore, the model parameters can be estimated based on data from walking experiments on treadmills. The approach is illustrated for data reported in the literature on walking experiments involving tilted floors. It is shown that attractor size depends on the floor inclination, which suggests that in general the domains of attraction of walking and running attractors are context dependent. In particular, they depend on floor inclination. In other words, a pattern formation model is presented that describes how sensory feedback about environmental conditions may impact gait control.